Data from: Morphology of western and semipalmated Sandpipers 1978-2020 ... - Ydenberg, Ronald; Fernández, Guillermo; Ortiz Lopez, Enver; Lank, David (Dryad, 2021)
Increasing predation danger can select for safety-enhancing modifications to prey morphology. We document multi-decade wing lengthening of a Pacific flyway migrant, the western sandpiper (Calidris mauri), and contrast this with contemporaneous wing shortening of the closely related semipalmated sandpiper (C. pusilla) on the Atlantic flyway. We measured > 12,000 southbound western sandpipers captured 1978–2020 at a major stopover site in British Columbia. Wing length increased at 0.074 mm y-1 (SE = 0.017; p < 0.0003) for adults, and 0.087 mm y-1 (SE = 0.029; p < 0.007) for juveniles. These rates are of similarly large magnitude (4–5% overall), but opposite in direction, to the rate we previously reported for semipalmated sandpiper adults (-0.103 mm y-1). In both species, the change is specific to wings rather than being part of general body size change. We interpret both trends as responses to the ongoing strong increase of peregrine falcon (Falco peregrinus) populations since the mid-1970s, an ... : Capture and morphological measurement of breeding and migrating semipalmated and western Sandpipers. Trends and effects on annual variation were modeled with linear models. ...